IMPLEMENTASI MANAJEMEN ISI KURIKULUM KARAKTER ISLAMI DI MADRASAH IBTIDAIYAH MIFTAHUL ULUM PULAU MANDANGIN SAMPANG - Moh. Zainuddin Syarif; Burdatun Warida (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2018)
The implementation of load management of the curriculum is packed with Islamicprograms which aim to develop the Islamic character of learners. By using casestudy method, it is known that the content of Islamic character curriculum contentin MI Miftahul Ulum Mandangin Island is applied with the addition of curriculumcharge in the development section self. On the charge MI Miftahul Ulum isimplementing a religious program. In addition, MI Miftahul Ulum also built anIslamic culture. The process of content management of Islamic charactercurriculum is also developed here. In the implementation of this also gotinhibiting factor and supporter. The changes in behaviors or outcomes of thisimplementation can be felt like the low violations committed by students, thereligious behavior that follow and the realization of a thick Islamic culture.